ПРОБЛЕМЫ УПРАВЛЕНИЯ ТУРКЕСТАНСКИМ ГЕНЕРАЛ-ГУБЕРНАТОРСТВОМ В КОЛОНИАЛЬНОЙ ПОЛИТИКЕ РОССИЙСКОЙ ИМПЕРИИ В КОНЦЕ XIX – НАЧАЛЕ ХХ ВВ - Шоев, И.Х. (SCIENCE and SOCIETY, 2022)
The article is devoted to a brief historical review of the problems of management of the Turkestan Governor-General in the colonial policy of the Russian Empire in the late XIX – early XX centuries, as well as the activities of management structures in the Turkestan region.